An Innovation in Picture Cards to Overcome Fear and Improve Arabic Vocabulary Memorization in Madrasah Ibtidaiyah Students - Lilik Nur Fadhilah (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2025)
Vocabulary mastery (mufradat) is the main foundation in Arabic language learning in Islamic Elementary Schools (MI). However, conventional rote learning methods often lead to language anxiety and passivity among digital generation students. This descriptive qualitative study aims to explore the implementation of modern physical flashcards combined with experiential learning and group games to overcome language anxiety and improve vocabulary mastery. The study subjects involved 25 third-grade students at MI Bandung III Jombang. Data were collected through structured participant observation, in-depth interviews with partner teachers, and analysis of field notes. The results showed that the integration of colorful modern flashcard visualizations and group game syntax successfully changed classroom dynamics positively. Students who initially showed symptoms of language anxiety such as passivity, fear of making mistakes, and avoiding eye contact became more confident, active, and enthusiastic in pronouncing new vocabulary collectively. In conclusion, the experiential and game-based approach using physical flashcards effectively creates a psychologically safe learning environment that enhances vocabulary memory retention for the alpha generation naturally without emotional stress.